"Slow science" for 21st century healthcare: reinventing health service research that serves fast-paced, high-complexity care organisations. Issue 6 (4th May 2021) - Jorm, Christine; Iedema, Rick; Piper, Donella; Goodwin, Nicholas; Searles, Andrew
Abstract : Purpose: The purpose of this paper is to argue for an improved conceptualisation of health service research, using Stengers' (2018) metaphor of "slow science" as a critical yardstick. Design/methodology/approach: The paper is structured in three parts. It first reviews the field of health services research and the approaches that dominate it. It then considers the healthcare research approaches whose principles and methodologies are more aligned with "slow science" before presenting a description of a "slow science" project in which the authors are currently engaged. Findings: Current approaches to health service research struggle to offer adequate resources for resolving frontline complexity, principally because they set more store by knowledge generalisation, disciplinary continuity and integrity and the consolidation of expertise, than by engaging with frontline complexity on its terms, negotiating issues with frontline staff and patients on their terms and framing findings and solutions in ways that key in to the in situ dynamics and complexities that define health service delivery. Originality/value: There is a need to engage in a paradigm shift that engages health services as co-researchers, prioritising practical change and local involvement over knowledge production. Economics is a research field where the products are of natural appeal to powerful health service managers. A "slow science" approach adopted by the embedded Economist Program with its emphasis on pre-implementation, knowledge mobilisation and parallel site capacity development sets out how research can be flexibly produced to improve health services.